The effects of parent training interventions on parental self-efficacy for parents with young children with an autism spectrum disorder or other developmental disabilities : a systematic review - Hohlfeld, Ameer Steven-Jörg (Department of Public Health and Family Medicine, 2016)
Background: A leading research priority worldwide is the need to improve the lives of those with disabilities through the effective development of interventions that can be carried out by non-specialists. Recent research has indicated that parent training interventions have shown to benefit both children with, and parents of children with disabilities. Aims: This systematic review sought to assess the effectiveness of interventions aimed at increasing parental self-efficacy levels in parents of young children with developmental disabilities. Methods and Procedures: We conducted a broad literature search across a number of databases to identify all relevant prospective studies meeting our study objective. Articles were selected using predefined criteria and data were extracted onto a purposely-designed data extracted form.